Labour Market Regulations and the Sectoral Reallocation of Workers: The Case of Trade Reforms - KAMBOUROV, GUEORGUI (Review of Economic Studies, 2009)
In this paper I highlight the importance of incorporating the institutional features of local labour markets into the analysis of trade reforms. A trade reform is often deemed beneficial because the elimination of trade barriers allows labour to reallocate towards those sectors in the economy in which the country has a comparative advantage. The amount and speed of the reallocation, however, and the post-reform behaviour of output, productivity and welfare, will depend on how regulated the labour market is. First, I document that high firing costs slow down the intersectoral reallocation of labour after a trade reform. Second, in order to isolate the effect of firing costs on labour reallocation, output and welfare after a trade reform, I build a dynamic general equilibrium model. I find that if a country does not liberalize its labour market at the outset of its trade reform, the intersectoral reallocation of workers will be 30% slower, and as much as 30% of the gains in real output and labour productivity in the years following the trade reform will be lost. From a policy standpoint, the message is that while trade reforms are desirable, they need to be complemented by labour market reforms in order to be fully successful.